Measuring Quality of Services - Šuster Erjavec Hana (Naše gospodarstvo/Our economy, 2012)
Dilemmas on how to conceptualize and operationalize quality of services are common in the literature. Our approach is inspired by the most advanced and promising scientific approaches to the conceptualization and operationalization of constructs. The implications of the focus groups showed how Slovenian consumers perceive quality of services. The empirical study on a sample of 1154 Slovenian consumers of three different types of services confirmed our operationalization of service quality that includes the experience of service quality on the whole, a comparison of how much the quality of services meets the actual expectations of service customers, and a comparison with the competition. This is an important methodological contributi- on to measuring service quality. Reliability of measuring all three variables is exem- plary in all three types of services; in addition, we confirmed the convergent validi- ty of the measurement.